2004
DOI: 10.1002/jmri.20097
|View full text |Cite
|
Sign up to set email alerts
|

Early heterogeneous enhancement of the liver: Magnetic resonance imaging findings and clinical significance

Abstract: Purpose:To investigate and assess the radiologic, serological, and histopathologic findings in patients who presented with early heterogeneous enhancement (EHE) on gadolinium-enhanced early-phase magnetic resonance imaging (MRI) of the liver. Materials and Methods:We searched our radiologic records of MRI of the liver from July 1999 to April 2002 to identify patients with EHE. Three investigators retrospectively evaluated in consensus the MR images in each patient for intensity and characteristic of EHE blinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
14
1
Order By: Relevance
“…86 Table 3 presents results of the imaging techniques used in diagnosis of NAFLD-NASH. 86,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] The underlying physical principle of imaging techniques are the same between adults and children. Consequently research in both age groups could be used to approve the use of these methods in pediatric field.…”
Section: Image Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…86 Table 3 presents results of the imaging techniques used in diagnosis of NAFLD-NASH. 86,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] The underlying physical principle of imaging techniques are the same between adults and children. Consequently research in both age groups could be used to approve the use of these methods in pediatric field.…”
Section: Image Studiesmentioning
confidence: 99%
“…88 The presence of early patchy enhancement in contrast agentenhanced (postgadolinium) MRI indicates either concurrent or recent hepatocellular damage, in contrast to late linear enhancement correlated with the presence of fibrosis. 97,98 Superparamagnetic iron oxide-enhanced MRI may be helpful for identifying NASH patients among patients suspected of having NAFLD by decreasing the signal from the nonfibrotic areas where Kupffer cells are present. 99 Magnetic resonance spectroscopy is probably the most accurate and fastest method of detecting fatty infiltration, but it is expensive, and the necessary software is still not easily available in most MRI units.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…An association with oral contraceptives has been reported, and some cases have been related to exposure to vinyl chloride 15] . Other possible etiologic factors have been suggested, such as hepatitis C 16] , chronic liver disease, alcohol abuse, sclerosing cholangitis 17] , major trauma to the liver, hormonal treatment, and occupational contaminants 12] . In our reported case, long-term oral contraceptive usage may be the etiologic factor.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that peribiliary enhancement occurs, in large part, as a result of inflammation and resultant capillary leakage of contrast material, with greater amounts of inflammation leading to greater degrees of capillary leakage [24]. Indeed, Kanematsu et al have found associations between early heterogeneous enhancement of the liver and inflammation, fibrosis, and hepatocellular necrosis [25]. A number of these processes are at work in PSC.…”
Section: Discussionmentioning
confidence: 99%